2006
DOI: 10.1175/jpo2949.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimates and Implications of Surface Eddy Diffusivity in the Southern Ocean Derived from Tracer Transport

Abstract: Near-surface “effective diffusivities” associated with geostrophic eddies in the Southern Ocean are estimated by numerically monitoring the lengthening of idealized tracer contours as they are strained by surface geostrophic flow observed by satellite altimetry. The resulting surface diffusivities show considerable spatial variability and are large (2000 m2 s−1) on the equatorward flank of the Antarctic Circumpolar Current and are small (500 m2 s−1) at the jet axis. Regions of high and low effective diffusivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
249
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(280 citation statements)
references
References 42 publications
29
249
2
Order By: Relevance
“…Estimates from observations (e.g. Ledwell et al, 1998;Bauer et al, 1998;Sundermeyer and Price, 1998;Zhurbas and Oh, 2003;Marshall et al, 2006) and high-resolution ocean models (e.g. Bryan et al, 1999;Eden, 2006;Eden et al, 2007) have revealed pronounced variability of eddy diffusivity in space and time.…”
Section: Neutral and Thickness Diffusivitymentioning
confidence: 99%
“…Estimates from observations (e.g. Ledwell et al, 1998;Bauer et al, 1998;Sundermeyer and Price, 1998;Zhurbas and Oh, 2003;Marshall et al, 2006) and high-resolution ocean models (e.g. Bryan et al, 1999;Eden, 2006;Eden et al, 2007) have revealed pronounced variability of eddy diffusivity in space and time.…”
Section: Neutral and Thickness Diffusivitymentioning
confidence: 99%
“…This suggests that eddy transport is greatest near the mean current itself, as eddy mixing scales with eddy kinetic energy (EKE ;Prandtl 1925;Holloway 1986). However, there is a growing body of evidence suggesting that the mean flow also suppresses mixing (e.g., Bower et al 1985;Nakamura and Ma 1997;Haynes and Shuckburgh 2000a,b;Allen and Nakamura 2001;Marshall et al 2006;Abernathey et al 2010;Ferrari and Nikurashin 2010). Thus assessing cross-jet transport involves finding the balance between the enhancement of mixing by instability and the suppression imposed by the mean.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we apply similar relations to an OGCM that is used to simulate tracer concentration from idealized pulse releases from the British nuclear fuel reprocessing plants at Sellafield and Dounreay. Advanced methods for extracting the equivalent diffusion have been developed and applied to both atmospheric (Haynes and Shuckburgh, 2000) and oceanic flows (Marshall et al, 2006), however, a simpler approach is taken here that is tailored for tracers with a point source release.…”
Section: Introductionmentioning
confidence: 99%